Análise de “Ideias para ensinar português para alunos surdos” - Seimetz-Rodrigues, Cristiane; Souza, Ana Cláudia de (Linguarum Arena, 2019)
This paper aims at presenting and analyzing the work for the instruction of written Portuguese, in the initial phase of literacy, for deaf students in the formal basic educational context, such as: Ideas to teach Portuguese to deaf students (Quadros & Schmiedt 2006). Qualitative assessments are performed, considering what the work conceptually presents and in what forms it proposes an implementation of the teaching of the Portuguese language regarding initial reading. The results indicate that, although this is an important work dedicated to one of the central aspects for promoting student school achievement: literacy, there is no evidence to allow teachers to guide themselves on how to conceive reading literacy, nor how to proceed in order to deaf students to read.